Core features of callous–unemotional traits: Network analysis of the inventory of callous–unemotional traits in offender and community samples. Issue 6 (25th November 2020) - Deng, Jiaxin; Wang, Meng‐Cheng; Shou, Yiyun; Gao, Yu
Abstract: Objective: Callous‐unemotional (CU) traits have been added as a specifier labeled with "Limited Prosocial Emotion" used to diagnose conduct disorder in the fifth edition of the  Diagnostic and Statistical Manual of Mental Disorders . However, little is known about the core features of CU traits. Thus, this study aimed to identify the most central component of CU traits from a network perspective. Method: Network analysis was applied to investigate the network structure of CU traits operationalized by the Inventory of Callous–Unemotional Traits in a sample of juvenile offenders ( M age  = 17.14, N  = 609) and community youths ( M age  = 10.82, N  = 487). Results: Our findings showed that items assessing callousness are the most central in the network across both samples. Also, the unemotional items were found to be located at a peripheral position, with fewer links apparent to callousness and uncaring items. Conclusions: Callousness might be the key feature of CU traits in youths. Our findings further advance the general understanding about the core features of CU traits in clinical practice.